Five decades of scientific development on "attachment theory": Trends and future landscape - Elaheh, Farahmand; Md Nor, Mariani; Abbas, Ghanbari Baghestan; Ale Ebrahim, Nader; Nasrin, Matinnia (Universiti Putra Malaysia, 2018)
Attachment Theory is one of the most frequently used frameworks which revolutionised the understanding of human behaviour, from early childhood to adulthood. Attachment Theory's scholarly output was examined using a quantitative bibliometric approach, based on rigorous facts extracted from the WoS databases from 1970 to 2017. Overall, 1,700 documents in the category "Psychology" with the topic "Attachment Theory" were analysed to find trends of publications, networking coupling, keywords frequencies, top authors, and highly cited papers. A qualitative content analysis of the top 20 documents with the highest average citation per year was done to provide insight on document approaches. The results show that the scientific productivity in "attachment theory" is highly skewed. The authors recommend publishing attachment theory related articles in an open access journal. There is a need for further interdisciplinary research and practice collaboration to move beyond the sole psychological approach and realise the importance of multi-disciplinary approaches.